1959
DOI: 10.2134/agronj1959.00021962005100120013x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Response to Gibberellic Acid of Dwarf, Semidwarf, and Standard Short and Tall Winter Wheat Varieties1

Abstract: Synopsis Four dwarf and semidwarf wheat varieties were not induced to attain a standard height by treatment with gibberellic acid, and they responded less to treatment than the standard‐height varieties. Optimum growth response occurred generally after injections with 100‐ppm of gibberellic acid, whereas inhibition was sometimes observed after treatment with 1000‐ppm. Spike emergence of 3 of the 6 varieties was hastened. Treatment affected internodes of three varieties differently depending on both variety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
3

Year Published

1975
1975
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 4 publications
2
31
0
3
Order By: Relevance
“…Making the same comparison on Wesley showed that this occurred but 1000 ppm GA 3 was needed ( Table 5). The data indicated that although Wesley was responsive, it required a higher GA 3 concentration than Goodstreak, supporting growth chamber findings [9], and studies on cultivar responses and the genetics of dwarfing [22]- [24]. A probable, partial explanation for the difference in GA 3 sensitivity between these two cultivars is that Wesley has the Rht8c and the Rht-B1b genes making it a semi-dwarf with limited endogenous GA 3 and sensitivity to applied GA 3 [15].…”
Section: Planting Date Comparisonssupporting
confidence: 58%
See 1 more Smart Citation
“…Making the same comparison on Wesley showed that this occurred but 1000 ppm GA 3 was needed ( Table 5). The data indicated that although Wesley was responsive, it required a higher GA 3 concentration than Goodstreak, supporting growth chamber findings [9], and studies on cultivar responses and the genetics of dwarfing [22]- [24]. A probable, partial explanation for the difference in GA 3 sensitivity between these two cultivars is that Wesley has the Rht8c and the Rht-B1b genes making it a semi-dwarf with limited endogenous GA 3 and sensitivity to applied GA 3 [15].…”
Section: Planting Date Comparisonssupporting
confidence: 58%
“…In earlier studies on applying GA 3 to wheat to stimulate stem or coleoptile elongation, the hormone was added to hydroponic solutions [21], injected weekly into the plant [22], soaked into germination paper [23], or applied to greenhouse soil to saturation [24]. These were greenhouse or growth chamber studies and would not be practical in a field situation or commercial use.…”
Section: Application Methodsmentioning
confidence: 99%
“…GIBBERELLIC ACID (GA) insensitivity for plant height in dwarf wheats, Triticum aestivum (2n = 6x = 42), has been described by Allan, Vogel and Craddock (1959), and has been shown to be associated with high endogenous levels of the hormone by Radley (1970). Other aspects of the GA insensitive reaction were described by Gale and Marshall (1973a) who showed that the dwarf varieties, Norm 1 0-Brevor 14, Tom Thumb and Minister Dwarf displayed a similar lack of response to GA in plant height, but an increased response in tiller production, the reverse of the reduced tillering response found in tall GA-sensitive varieties.…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION SOME dwarf wheats (Triticum aestivum, 2n = 6x = 42) differ from tall wheats in their lack of response to applied gibberellin (GA). Allan, Vogel and Craddock (1959) first indicated an insensitive reaction to exogenous GA in dwarf and semi-dwarf varieties. Radley (1970), using semi-dwarf spring wheat cultivars derived from the Japenese variety Norm 10, showed that these genotypes had higher endogenous GA levels than control tall varieties.…”
mentioning
confidence: 99%